Processing of human toll-like receptor 7 by furin-like proprotein convertases is required for its accumulation and activity in endosomes. - Hipp, M; Shepherd, D; Gileadi, U; Aichinger, M; Kessler, B; Edelmann, M; Essalmani, R; Seidah, N; Reis e Sousa, C; Cerundolo, V (2013)
Toll-like receptor 7 (TLR7) triggers antiviral immune responses by recognizing viral single-stranded RNA in endosomes, but the biosynthetic pathway of human TLR7 (hTLR7) remains unclear. Here, we show that hTLR7 is proteolytically processed and that the C-terminal fragment selectively accumulates in endocytic compartments. hTLR7 processing occurred at neutral pH and was dependent on furin-like proprotein convertases (PCs). Furthermore, TLR7 processing was required for its functional response to TLR7 agonists such as R837 or influenza virus. Notably, proinflammatory and differentiation stimuli increased the expression of furin-like PCs in immune cells, suggesting a positive feedback mechanism for TLR7 processing during infection. Because self-RNA can under certain conditions activate TLR7 and trigger autoimmunity, our results identify furin-like PCs as a possible target to attenuate TLR7-dependent autoimmunity and other immune pathologies.